Knots in the Discourse of Innovation: Investigating Multiple Tensions in a Reacquired Spin-off. Issue 3 (April 2017) - Sheep, Mathew L.; Fairhurst, Gail T.; Khazanchi, Shalini
We examine the case of a corporate spin-off, in which its reacquisition by the parent firm radically changed its structure and culture. Employing a discourse lens, we study paradoxical tensions of innovation as key members "talk into being" the paradoxical circumstances of their environment. From our analysis, we develop the concept of tensional "knots, " discursive formulations in which members construct tensions, not only as co-occurring, but as Gordian (inseparable) entanglements of interdependence. Knotted tensions can be amplifying (exacerbating) or attenuating (improving) in their effects on one another, but with very different consequences to innovative action. Specifically, knotted tensions and the way in which members manage them set up counter-intuitive logics that serve to justify courses of innovative action or inaction. We propose a process model advancing understanding of interlinked tensions in more complex ways than current paradox theory allows. We conclude with a discussion of our contributions to paradox theory in innovative contexts, along with suggestions for future research.